2010
DOI: 10.1074/jbc.m110.139667
|View full text |Cite
|
Sign up to set email alerts
|

Structural Requirements for Activation in αIIbβ3 Integrin

Abstract: Integrins are postulated to undergo structural rearrangement from a low affinity bent conformer to a high affinity extended conformer upon activation. However, some reports have shown that a bent conformer is capable of binding a ligand, whereas another report has shown that integrin extension does not absolutely lead to activation. To clarify whether integrin affinity is indeed regulated by the so-called switchblade-like movement, we have engineered a series of mutant ␣IIb␤3 integrins that are constrained spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 33 publications
5
40
0
Order By: Relevance
“…Glycan wedge mutations that enforce and disulfide mutations that restrain the hybrid domain swinging out activated and deactivated integrin, respectively (Luo et al, 2003;Kamata et al, 2010). In addition, mutations enforcing integrin extension but restraining the swing-out of the hybrid domain did not activate integrin (Kamata et al, 2010). A recent study showed that talin1 alone only induces integrin extension with intermediate affinity for b2 integrin, whereas both talin1 and kindlin-3 are required to induce the open headpiece, high-affinity conformation (Lefort et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycan wedge mutations that enforce and disulfide mutations that restrain the hybrid domain swinging out activated and deactivated integrin, respectively (Luo et al, 2003;Kamata et al, 2010). In addition, mutations enforcing integrin extension but restraining the swing-out of the hybrid domain did not activate integrin (Kamata et al, 2010). A recent study showed that talin1 alone only induces integrin extension with intermediate affinity for b2 integrin, whereas both talin1 and kindlin-3 are required to induce the open headpiece, high-affinity conformation (Lefort et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations that favor the downward movement of the b6-a7 loop and a7-helix constitutively activated integrin for ligand binding (Luo et al, 2004b;Yang et al, 2004;Cheng et al, 2007). Glycan wedge mutations that enforce and disulfide mutations that restrain the hybrid domain swinging out activated and deactivated integrin, respectively (Luo et al, 2003;Kamata et al, 2010). In addition, mutations enforcing integrin extension but restraining the swing-out of the hybrid domain did not activate integrin (Kamata et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the postulated "dead bolt" interaction that prevents integrin extension buries an insignificant surface area of only 40 Å 2 in ␣ V ␤ 3 (23) and is not present in ␣ IIb ␤ 3 or ␣ x ␤ 2 , and its mutation in ␣ V ␤ 3 and ␣ IIb ␤ 3 has no effect on their ligand binding capacities (10,24). Disulfide bonds in multiple locations to favor the bent conformation or closed headpiece and glycan wedges to stabilize extension and headpiece opening all support a requirement for integrin extension and headpiece opening for activation and the insufficiency of the bent conformation (11,(25)(26)(27).…”
mentioning
confidence: 99%
“…Sixth, 3D molecular models have been built based on crystallographic and NMR data to analyze the effects of novel amino acid substitutions on receptor structure and function and the generation of alloantigens (15,(46)(47)(48)(49)(50)(51)(52)(53). The data from these models and assessments of the severity of the amino acid change in the variants have the potential to aid in predicting whether a novel variant is likely to affect receptor function and immunogenicity (54)(55)(56)(57)(58)(59).…”
mentioning
confidence: 99%